Pengaruh Celebrity Endorser dan Iklan Vidio terhadap Brand Image Produk Pembersih Wajah Garnier pada Mahasiswi Universitas Negeri Padang - Khofifah Nur; Rose Rahmidani (Universitas Negeri Padang, 2020)
The purpose of researche is to know the effect of celebrity endorser and video advertising on brand image face lightening product of Garnier Lingh Complete Super Foam. This research used causative form, the population in this research were students of State University of Padang. Number of samples were decided base on hair et. As many as 100 people and were chosen by using proportional sampling method and purposive sampling technic. Data were used is primer data were provided through questionnaire shared to students of State University of Padang based on predetermined criteria. Analysis method was used is multiple regression by using spss 2. The result of this research shows (1) celebrity endorser and video advertising any significant effect to brand image, (2) celebrity endosrser have no significant affect on brand image, (3) audio visual advertising have significant effect on brnad image Keywords: celebrity endorser, video edvertising, brand image